AFIKS PEMBENTUK VERBA DALAM BAHASA BUGIS PADA KARANGAN BEBAS SISWA KELAS VII SMP MUHAMMADIYAH SOPPENG - Dini, Dini; Syamsudduha, Syamsudduha; Hajrah, Hajrah (Journal Studies in Indonesian Language and Literature, 2024)
This research is a descriptive qualitative research which aims to describe the types and meanings of verb-forming affixes in Bugis language in students' free essays. Data and data sources in this research are written data in the form of words containing verb-forming affixes. The data collection technique used in this research is document analysis which is morphological study with note-taking technique. The analysis technique includes data reduction, data presentation and conclusion drawing. Based on the results of data analysis, the types and meanings of verb-forming affixes in students' free essays were found. (1) types of verb-forming affixes in Bugis language, namely prefix maG-, mappa-, mappasi-, infix -ul-, suffix -i-, confix pa-...-i. (2) The meaning of affixes forming verbs in Bugis language, namely prefix maG-, doing an action, mappa- making an activity. The meaning of the infix -ul- to do an action. The meaning of the suffix -i, states the command and means to cause as mentioned in the base word. The meaning of the confix pa-...-i, means to make something.